Eco-friendly and simple synthesis of some non-natural flavones through chalcones - Rahman, Mohammad Saidur; Alam, Sayeda Shakila; Happy, Kamrunnahar; Hossain, Mohammad Mamun; Islam, Mohammad Khademul; Biswas, Foni Bushon (European Journal of Chemistry, 2018)
A distinctive feature of polyphenolics is the possession of biological properties such as antioxidant and antimicrobial activities. Simple synthesis and study about such important class of compounds and their analogs are very important to enhance the understanding of their role in human health and diseases. Accordingly, a series of chalcones (2a-f) have been synthesized by Claisen-Schmidt condensation reaction with required acetophenones and aromatic aldehydes in high yields. The conversion of chalcones to the corresponding flavones (1a-g) taking minimal amount of dimethyl sulfoxide with iodine in presence of sulfuric acid was carried out under microwave conditions in high yields.